Coverage of Large-Scale Food Fortification of Edible Oil, Wheat Flour, and Maize Flour Varies Greatly by Vehicle and Country but Is Consistently Lower among the Most Vulnerable: Results from Coverage Surveys in 8 Countries. Issue 5 (12th April 2017) - Aaron, Grant J; Friesen, Valerie M; Jungjohann, Svenja; Garrett, Greg S; Neufeld, Lynnette M; Myatt, Mark
Abstract: Background: Large-scale food fortification (LSFF) of commonly consumed food vehicles is widely implemented in low- and middle-income countries. Many programs have monitoring information gaps and most countries fail to assess program coverage. Objective: The aim of this work was to present LSFF coverage survey findings (overall and in vulnerable populations) from 18 programs (7 wheat flour, 4 maize flour, and 7 edible oil programs) conducted in 8 countries between 2013 and 2015. Methods: A Fortification Assessment Coverage Toolkit (FACT) was developed to standardize the assessments. Three indicators were used to assess the relations between coverage and vulnerability: 1 ) poverty, 2 ) poor dietary diversity, and 3 ) rural residence. Three measures of coverage were assessed: 1 ) consumption of the vehicle, 2 ) consumption of a fortifiable vehicle, and 3 ) consumption of a fortified vehicle. Individual program performance was assessed based on the following: 1 ) achieving overall coverage ≥50%, 2) achieving coverage of ≥75% in ≥1 vulnerable group, and 3 ) achieving equity in coverage for ≥1 vulnerable group. Results: Coverage varied widely by food vehicle and country. Only 2 of the 18 LSFF programs assessed met all 3 program performance criteria. The 2 main program bottlenecks were a poor choice of vehicle and failure to fortify a fortifiable vehicle (i.e., absence of fortification). Conclusions: The results highlight the importance of sound program design and routine monitoring and evaluation. There is strong evidence of the impact and cost-effectiveness of LSFF; however, impact can only be achieved when the necessary activities and processes during program design and implementation are followed. The FACT approach fills an important gap in the availability of standardized tools. The LSFF programs assessed here need to be re-evaluated to determine whether to further invest in the programs, whether other vehicles are appropriate, and whether other approaches are needed.